Atkins' molecules - Atkins, Peter (Cambridge University Press, 2003)
In this new edition of the book that was called "the most beautiful chemistry book ever written," Peter Atkins reveals the molecules responsible for the experiences of our everyday life in fabrics, drugs, plastics, explosives, detergents, fragrances, tastes, and sex. Atkins gives a non-technical account of a range of aspects of the world around us, revealing unexpected connections and insight into how it can be understood in terms of the atoms and molecules from which it is built. This new edition has dozens of new molecules, new graphic presentations, and a more accessible account of the molecules themselves. Peter Atkins is SmithKline Beecham Fellow and Tutor in Physical Chemistry at Oxford University. Atkins' research includes the fields of theoretical chemistry, particularly magnetic resonance and the electromagnetic properties of molecules.